Pengaruh Konseling Apoteker Terhadap Hasil Terapi Pasien Hipertensi di Poliklinik Penyakit Dalam RSUD Kraton Kabupaten Pekalongan - Anita Budi Mulyasih Djoko Wahyono I Dewa Putu Pramantara (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2012)
Prevalence of Hypertension increased in line with changes of life style as smoking, obesity, non physical activity, psycho-social stress in many countries. Comprehensive and intensive treatment could be more control of blood pressure. Understood, knowledge and adherence of patient expected will improve along with act of distributed useful and correct information by pharmacist. The aim this study to determine the effect of counseling pharmacist on therapeutic outcomes and adherence and to know the correlation between therapeutic outcomes and adherence of outpatients hypertensive in the internal disease clinic at RSUD Kraton Pekalongan District. This research was experimental intervention with pre-post intervention with randomized without matching. Data was collected by prospective method. The control group given a leaflet at the first month, and the intervention group given a leaflet at the first month and counseling every early month, during 3 months.There was 75 patients, the intervention group (N=39) experienced a significant decrease in blood pressure at the end of the study, on systolic amounted 11.28±8.33 mmHg [P=0.000(P<0.05)] and diastolic amounted 7.18±6.86 mmHg [P=0.000(P<0.05)], whereas in the control group (N=36) did not experience a significant decrease in blood pressure is systolic amounted 2.22±10.45 mmHg [P=0.203(P>0.05)] and diastolic amounted 0.28±6.09 mmHg [P=0.782(P>0.05)]. Adherence of patients as measured by MMAS scale in the intervention group better adherence than the control group (33.33% : 2.78%). There was have correlation a means between MMAS score with change of systolic (P=0.019; r=0.270) and diastolic (P=0.001; r=0.372) which positive direction. It was concluded that counseling has an effect on adherence positively in the intervention group better than the control group and decreasing systolic and diastolic blood pressure until reach targets. There was a close correlation between decrease in blood pressure with MMAS score in hypertensive patients.